KEMAMPUAN SERAPAN ABU TULANG KAMBING TERHADAP VARIASI KONSENTRASI ION SULFAT - R. Fitryani; S. Bali; Itnawita ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Calcium oxide was a major component in bone ash. This calcium oxide has relativelyopened structure, so it can be used as an adsorbent. Its adsorption ability on sulfate ionhas been analyzed in an solution. The analysis of sulfate ion was carried out usingSpectrophotometer UV-VIS by turbidimetry method. The results showed thatconcentration of bone ash affected to the adsorption of sulfate ion with optimumadsorption of 80.833% at 10 ppm of bone ash.